Cereblon gene expression and correlation with clinical outcomes in patients with relapsed/refractory multiple myeloma treated with pomalidomide: an analysis of STRATUS. Issue 2 (28th January 2019) - Qian, Xiaozhong; Dimopoulos, Meletios A.; Amatangelo, Michael; Bjorklund, Chad; Towfic, Fadi; Flynt, Erin; Weisel, Katja C.; Ocio, Enrique M.; Yu, Xin; Peluso, Teresa; Sternas, Lars; Zaki, Mohamed; et al.
Abstract: We analyzed gene expression levels of CRBN, cMYC, IRF4, BLIMP1, and XBP1 in 224 patients with multiple myeloma treated with pomalidomide and low-dose dexamethasone in the STRATUS study (ClinicalTrials.gov: NCT01712789; EudraCT number: 2012-001888-78). Clinical responses were observed at all CRBN expression levels. A trend in progression-free survival (PFS; p  = .038) and a potential trend in overall survival (OS; p  = .059) favoring high CRBN expressers were observed; however, no notable difference in overall response rate (ORR) was observed. ORR (30%), median PFS (17.7 weeks), and median OS (52.3 weeks) in low- CRBN expressers were comparable to those in the STRATUS intent-to-treat population (ORR, 33%; median PFS, 20.0 weeks; median OS, 51.7 weeks). A trend in ORR ( p  = .050) favoring higher cMYC expressers was observed with no notable difference in PFS or OS. This analysis does not support exploring CRBN as a biomarker for selecting patients for pomalidomide therapy. Trial registration: ClinicalTrials.gov identifier: NCT01712789.